COVID-19 Testing and Infection Surveillance: Is a Combined Digital Contact Tracing and Mass Testing Solution Feasible in the United States? (2020)
In December 2019, the novel COVID-19 virus spread from a cluster of pneumonia cases in Wuhan, China to every corner of the globe creating a worldwide pandemic pushing hospital systems past capacity and bringing economies worldwide to a halt. The COVID-19 pandemic is unique in comparison to prior coronavirus epidemics in its superior ability to be spread by asymptomatic and pre-symptomatic patients allowing the virus to silently evade traditional symptoms-based screening approaches. Countries have implemented cutting-edge digital solutions to enhance traditional contact tracing methodologies in combination with novel testing strategies to combat the virus with variable levels of success. Despite having one of the most advanced and expensive health care systems in the world, the United States (U.S.) response is arguably one of the world’s largest failures as it leads the globe in case number as well as deaths. Until a successful vaccine can be broadly distributed, it is imperative the U.S. curbs the viral spread by rapidly developing a framework implementing both enhanced tracing and testing strategies balancing the needs of public health while respecting individual liberties. This review will explore the role of technology augmented contact-based surveillance in tracking the outbreak in select countries in comparison to the current U.S. approach. It will evaluate barriers in the US to implementing similar technologies focusing on privacy concerns and a lack of unified testing and tracing strategy. Finally, it will explore strategies for rapidly scaling testing in a cost-effective manner.